Immune checkpoint inhibition therapy for advanced skin cancer in patients with concomitant hematological malignancy: a retrospective multicenter DeCOG study of 84 patients - Leiter-Stöppke, Ulrike; Loquai, Carmen; Reinhardt, Lydia; Rafei-Shamsabadi, David; Gutzmer, Ralf; Kaehler, Katharina; Heinzerling, Lucie; Hassel, Jessica C.; Glutsch, Valerie; Sirokay, Judith; Schlecht, Nora; Rubben, Albert; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Skin cancers are known for their strong immunogenicity, which may contribute to a high treatment efficacy of immune checkpoint inhibition (ICI). However, a considerable proportion of patients with skin cancer is immuno-compromised by concomitant diseases. Due to their previous exclusion from clinical trials, the ICI treatment efficacy is poorly investigated in these patients. The present study analyzed the ICI treatment outcome in advanced patients with skin cancer with a concomitant hematological malignancy. Methods This retrospective multicenter study included patients who were treated with ICI for locally advanced or metastatic melanoma (MM), cutaneous squamous cell carcinoma (cSCC), or Merkel cell carcinoma (MCC), and had a previous diagnosis of a hematological malignancy irrespective of disease activity or need of therapy at ICI treatment start. Comparator patient cohorts without concomitant hematological malignancy were extracted from the prospective multicenter skin cancer registry ADOREG. Treatment outcome was measured as best overall response, progression-free (PFS), and overall survival (OS). Results 84 patients (MM, n=52; cSCC, n=15; MCC, n=17) with concomitant hematological malignancy were identified at 20 skin cancer centers. The most frequent concomitant hematological malignancies were non-Hodgkin's lymphoma (n=70), with chronic lymphocytic leukemia (n=32) being the largest entity. While 9 patients received ICI in an adjuvant setting, 75 patients were treated for advanced non-resectable disease (55 anti-PD-1; 8 anti-PD-L1; 5 anti-CTLA-4; 7 combinations). In the latter 75 patients, best objective response (complete response+partial response) was 28.0%, disease stabilization was 25.3%, and 38.6% showed progressive disease (PD). Subdivided by skin cancer entity, best objective response was 31.1% (MM), 26.7% (cSCC), and 18.8% (MCC). Median PFS was 8.4 months (MM), 4.0 months (cSCC), and 5.7 months (MCC). 1-year OS rates were 78.4% (MM), 65.8% (cSCC), and 47.4% (MCC). Comparison with respective ADOREG patient cohorts without hematological malignancy (n=392) revealed no relevant differences in ICI therapy outcome for MM and MCC, but a significantly reduced PFS for cSCC (p=0.002). Conclusions ICI therapy showed efficacy in advanced patients with skin cancer with a concomitant hematological malignancy. Compared with patients without hematological malignancy, the observed ICI therapy outcome was impaired in cSCC, but not in MM or MCC patients.
Gesehen am 22.01.2020